Optimization of heat shock temperature and time on the transformation of pRGEB32 into Escherichia coli DH5ÃÂ± - Rosy Feraningsih Patigu; Putri Wijayanti; Alfino Sebastian; Yekti Asih Purwestri (Jurnal Biologi Tropis, 2021)
Genome editing technique is one of the methods for studying the expression of gene, eliminating unfavorable traits or phenotypes and generating the new characters of species. The pRGEB32 plasmid is one of the vectors that used in genome editing with carrying the Cas9 gene, restriction site of sgRNA (single guide RNA) and specific promoters that can be expressed in plants. The first step in the genome editing process is inserting pRGEB32 into Escherichia coli for propagation. The large size of the plasmid molecule becomes a challenge to determine the right method in the transformation process. This study aims to determine the temperature and time of heat shock transformation of plasmid pRGEB32 into E. coli. The transformation of pRGEB32 into plasmids was carried out with variations in temperature and time, 42Ã¢âÆ (30 seconds and 60 seconds) and 55Ã¢âÆ (30 seconds and 60 seconds). The results showed that a heat shock temperature of 55Ã¢âÆ with a time of 60 seconds was the best temperature for the transformation of pRGEB32 into E. coli. This optimization of heat shock condition will increase the transformation efficiency, which is in the range of 3322-10.989 cfu/ÃÂµg.ÃÂ